A vallási térszerkezet változása a Vajdaságban 1944-től napjainkig - M. Császár, Zsuzsanna (Közép-Európai Közlemények, 2011)
In the East-Central and Southeast European region the relationship between religion and national identity is very strong and look back relatively long historical period to (thinking of the struggles against the Turkish cohesive strength of Christianity, or the anti-Habsburg Hungarian Reformed Church and intensifying engagement). Particulary in the multi-ethnic areas can obsereve the strengthening role of the separation of religions from another ethnicity to their own identities. Several examples of events in the wider region could take to illustrate how national identification used the religious symbols, or the church itself. Not only the ethnic minority groups have found the power of religion, but also for the majority created autonomy is required the discrimination of minorities in the spirit of religion and the Church’s role in support. Vojvodina –today the northern-most province of Serbia –was in the past under several state’s sovereignty for centuries, became by migrations during the first world war one of Europe’s most multiethnic and multireligious area. The region is an ethnic, religious and cultural contact zone. Here contacts the two major branches of Christianity, the Eastern and Western Church, and Islam, but more than half a century ago the Judaism was also remarkable.